Evaluation of the air quality in arid climate megacities (Case study: Greater Cairo) - HWEHY, Mohammed Mahmoud A.; MOURSY, Fawzia Ibrahim; EL-TANTAWI, Attia Mahmoud; MOHAMED, Mostafa Abd El-Hameed (Contributions to Geophysics and Geodesy, 2024)
The accelerated urbanization in the last decade and population growth in developing countries in the Middle East and North Africa (MENA) region have increased the count of humans exposed to air pollution. This work aims to provide an insight into air quality in the Greater Cairo (GC) area which is one of the largest megacities in the MENA region and is classified as its most polluted city according to the reports of the World Health Organization (WHO). Exploratory data analysis and cluster analysis were used to assess the pollutants data and meteorological data to understand the impacts of weather factors on air quality in GC. According to the results, GC suffers from particle matter of 10 micrometres or less (PM10) pollutants. The annual averages ranged from 97 ± 10 to 203 ± 42 μg/m3. Though short-term exposure to gaseous pollutants did not exceed the limits, the long-term exposures exceeded those in some congested traffic areas. The annual averages ranged from 20 ± 5 to 63 ± 24 μg/m3 for Nitrogen dioxide (NO2) and from 9 ± 3 to 21 ± 5 μg/m3 for sulphur dioxide (SO2). Also, the terrain affects the spatial variation of pollutants observation. There is a negative correlation between the monitoring site elevation and the pollutant concentration.